Matrix-assisted laser desorption/ionization time of flight mass spectrometry for comprehensive indexing of East African Ixodid tick species - Rothen, J.; Githaka, Naftaly W.; Kanduma, Esther G.; Olds, Cassandra L.; Pflueger, V.; Mwaura, S.; Bishop, Richard P.; Daubenberger, C.A. (Springer, 2016)
The tick population of Africa includes several important genera belonging to the family Ixodidae. Many of these ticks are vectors of protozoan and rickettsial pathogens including Theileria parva that causes East Coast fever, a debilitating cattle disease endemic to eastern, central and southern Africa. Effective surveillance of tick-borne pathogens depends on accurate identification and mapping of their tick vectors. A simple and reproducible technique for rapid and reliable differentiation of large numbers of closely related field-collected ticks, which are often difficult and tedious to discriminate purely by morphology, will be an essential component of this strategy. Matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) is increasingly becoming a useful tool in arthropod identification and has the potential to overcome the limitations of classical morphology-based species identification. In this study, we applied MALDI-TOF MS to a collection of laboratory and field ticks found in Eastern Africa. The objective was to determine the utility of this proteomic tool for reliable species identification of closely related afrotropical ticks.